(untitled) (Texas Journal of Philology, Culture and History, 2023)
Culture is a tool that speaks about the past, present and future of a nation and introduces it to the world. This article talks about the attention paid to the field of culture and art in the modernizing Uzbekistan, the measures that are being implemented and planned to be implemented in the future